Denmark : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Alternate Executive Director for Denmark. (IMF Staff Country Reports; Country Report ;, 2022)
The strength of the economic recovery bodes well for the rebound in activity to persist, but uncertainty remains high due to the war in Ukraine and the pandemic, with risks tilted to the downside. With employment above pre-pandemic levels, however, labor market pressures have increased. High energy prices have propelled inflation to a historic high. The current account remains elevated. High household debt constitutes a key source of risk as house price growth remains strong.